Adequacy of information provided in the informed consent to patients undergoing surgery at a tertiary care hospital - Joshi, Arabind; Bhandary, Shital; Maharjan, Rony; Sah, Mukesh Kumar (Journal of General Practice and Emergency Medicine of Nepal, 2021)
Introduction: Informed consent gives patient assurance and faith by providing information on diagnostic and therapeutic methods, risks, cost, complications, and alternative treatment options. This study aims to determine the adequacy of information provided in preoperative informed consent in everyday practice. Method: A cross sectional study was conducted among 388 patients undergoing surgery at Patan Hospital from November, 2016 to April, 2017. Respondents’ characteristics with Adequacy of information scale (AOI scale) were evaluated. Frequency, percentage, mean and standard deviation were calculated for descriptive study while Student t-test and ANOVA test was applied for assessing association between categorical variables. P value less than 0.05 was considered statistically significant. Result: Among participants 52.6% were females and 47.4% males with mean age of 40.69 years. Most of the patients were literate and with higher education. Male patients, exhibit a statistically significant higher AOI scale (p value <0.001) then females. Illiterates and people with higher education had statistically significant lower mean AOI scales (p value <0.001) compared to literates. A high mean AOI scale was associated with active involvement of both the surgeon and the patient in the decision-making process (p value <0.0001). Even among patients satisfied with consent process mean AOI scale was low (4.30=53.75%). The mean AOI scale did not differ significantly amongst patients of different ages, marital status, religion or caste. Conclusion: There is a need of improving the preoperative informed consent process as adequacy of information provided is still lacking.